ANALISIS SPASIAL DAN DISTRIBUSI PENYAKIT TUBERKULOSIS PARU ANAK DI KOTA DENPASAR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Dewi Prativi, I Gusti Ayu Adinda; Astuti, Putu Ayu Swandewi (ARCHIVE OF COMMUNITY HEALTH, 2025)
Childhood pulmonary TB are often neglected because of low transmission. The purpose of this study was spatially analyze of childhood pulmonary TB and know its distribution in Denpasar on time 2020-2022. The research design is an ecological study using GIS in observation for 2020-2022 The sample was childhood pulmonary TB and primary health facilities in Denpasar which selected based on total sampling. The data source is secondary data. The result showed that there were 25 cases in 2020, 15 cases in 2021, dan 69 cases in 2022. The patterns of distribution of cases were dispersed (2020), random (2021), and dispersed again (2022). All primary health facilities have coverage under 90%, except in 2020 there is one above 90%. There was no correlation between CNR of childhood pulmonary TB with CNR of adult TB and population density (p>0,05). Keywords: Childhood pulmonary TB, CNR, Patterns, Population density, Spatial analysis